Pigment-binder interactions in calcium-based tempera paints. (January 2018) - Elert, Kerstin; Herrera, Agustin; Cardell, Carolina
Abstract: Calcium hydroxide and calcium carbonate, or mixtures of both have been used for millennia as pigments or primers, often in combination with proteinaceous binders. Despite their historical importance and widespread use in wall paintings, little research has been dedicated to possible interactions between the inorganic pigment and the organic binder, and their impact on paint aging under variable environmental conditions. Here, paint dosimeters mimicking historic paints were exposed to artificial UV-aging and long-term outdoor exposure tests and analyzed using a wide array of techniques, including x-ray diffraction, scanning electron microscopy, attenuated total reflectance-Fourier transform infrared spectroscopy, thermogravimetry, laser particle size analysis, and spectrophotometry. Our results show that the prevailing environmental conditions (i.e., sheltered or directly exposed to rain and sunlight) and the presence or absence of proteinaceous binder have a significant influence on the mineralogical and morphological evolution of paints containing calcium hydroxide. The organic binder delays carbonation and induces the formation of hybrid materials similar to biominerals, incorporating organics into the inorganic carbonate matrix. Such a biomimetic effect significantly enhances the durability of the paint layer. Calcium carbonate pigments, in contrast, did not suffer mineralogical changes in the presence of organic binder. However, both, calcium carbonate and hydroxide caused conformational changes in the proteinaceous binder. Observed differences in pigment-binder interactions have an important influence on the paints' resistance to chemical weathering, explain different alteration patterns observed in historic paints under semi-open exposure conditions, and allow for recommendations regarding the most suitable material for wall painting conservation considering the prevailing environmental conditions. Highlights: Formation of organo-metal hybrid materials in calcium-based tempera paints. Organo-metal materials increase weather resistance of calcium-based paints. Proteinaceous binder reduces carbonation rate of portlandite. Stabilization of metastable calcium carbonate phases due to rabbit glue. Calcium-based pigments cause conformational changes in rabbit glue.